Voice assessment: updates on perceptual, acoustic, aerodynamic, and endoscopic imaging methods - Daryush D. Mehta; Robert E. Hillman (2008)
Purpose of review This paper describes recent advances in perceptual, acoustic, aerodynamic, and endoscopic imaging methods for assessing voice function. Recent findings We review advances from four major areas. Perceptual assessment: Speech-language pathologists are being encouraged to use the new consensus auditory-perceptual evaluation of voice inventory for auditory-perceptual assessment of voice quality, and recent studies have provided new insights into listener reliability issues that have plagued subjective perceptual judgments of voice quality. Acoustic assessment: Progress is being made on the development of algorithms that are more robust for analyzing disordered voices, including the capability to extract voice quality-related measures from running speech segments. Aerodynamic assessment: New devices for measuring phonation threshold air pressures and air flows have the potential to serve as sensitive indices of glottal phonatory conditions, and recent developments in aeroacoustic theory may provide new insights into laryngeal sound production mechanisms. Endoscopic imaging: The increased light sensitivity of new ultra high-speed color digital video processors is enabling high-quality endoscopic imaging of vocal fold tissue motion at unprecedented image capture rates, which promises to provide new insights into the mechanisms of normal and disordered voice production. Summary Some of the recent research advances in voice function assessment could be more readily adopted into clinical practice, whereas others will require further development.